the Pengembangan E-modul Pembelajaran Berbasis Google Sites Pada Mata Pelajaran Gambar Teknik Otomotif Kelas X di SMK Muhammadiyah Gamping: Pengembangan E-modul Pembelajaran Berbasis Google Sites Pada Mata Pelajaran Gambar Teknik Otomotif Kelas X di SMK Muhammadiyah Gamping - Adila Oktaviyani; Widodo Widodo (Jurnal Taman Vokasi, 2025)
The purpose of this study was to design a Google Sites-based e-module for use in the Engineering Drawing class of SMK Muhammadiyah Gamping for tenth-grade students. Students had difficulty understanding the concept because the printed module was static, according to the needs analysis. This study used the 4D model, which stands for "Define," "Design," "Develop," and "Diseminate," to conduct its research and development. Observations and interviews were used to examine needs at the define stage. The structure of the E-module was created during the design phase by including multimedia components such as photos and movies. Expert validation and student trials conducted during development indicated that the E-module was quite practical in terms of content, media, and learning efficacy. Students' engagement, comprehension, and capacity for independent learning were all positively influenced by the E-module built on Google Sites, thanks to its customizable and dynamic content presentation. This study makes an important contribution to the ongoing efforts of the vocational education field to innovate its teaching media for the digital era.